Patient-provider communication during second opinion consultations in oncology. Issue 10 (October 2021) - Lehmann, Vicky; Smets, Ellen M.A.; de Jong, Maxime; de Vos, Filip Y.F.; Stouthard, Jacqueline M.; Hillen, Marij A.
Abstract: Objective: Providing a second opinion (SO) in oncology is complex, and communication during SOs remains poorly understood. This study aimed to systematically observe how patients and oncologists communicate about SO-specific topics (i.e., patient motivation, the referring oncologist, treatment transfer/back-referral), and how such communication affects patient satisfaction. Methods: A prospective mixed-methods study of cancer patients seeking a SO ( N = 69) and consulting oncologists was conducted. Before the SO, patients reported their expected place of future treatment. Following the SO, patients' and oncologists' satisfaction was assessed. All SOs were audio-recorded. Absolute and relative duration of SO-specific talk were calculated and specific events (e.g., questions/utterances) were coded (incl. valence, explicitness). Results: SOs lasted 19–73 min, of which 3.7% was spent discussing motivations. Oncologists rarely explored patients' motivations. Talk about referring oncologists (12.5% of consultation) was mostly critical by patients ( M = 43.0%), but positive/confirming by consulting oncologists ( M = 73.5%). Although 22.2% of patients expected a treatment transfer, this topic (3.3% of consultation time) was rarely explicitly discussed. Patients who were referred back were significantly less satisfied ( d = 0.85). Conclusion: Patient-provider communication in oncological SOs appears insufficiently aligned. Practice Implications: Patients and oncologists need support to explicitly and productively communicate about SO-specific topics and to better manage expectations. Recommendations are provided.